1979
DOI: 10.1113/jphysiol.1979.sp012843
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative description of membrane currents in rabbit myelinated nerve.

Abstract: 1. Voltage‐clamp studies were carried out on single rabbit myelinated nerve fibres at 14 degrees C with the method of Dodge & Frankenhaeuser (1958). 2. A method was developed to allow the ionic currents through the modal membrane to be calibrated exactly under voltage‐clamp conditions by measuring the resistance of the internode through which the current was injected. 3. The ionic currents in a rabbit node of Ranvier can be resolved into two components, a sodium current and a leak current. Potassium current is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
261
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(281 citation statements)
references
References 20 publications
13
261
0
1
Order By: Relevance
“…In addition, 100 j, tmol/1 4-AP clearly enhanced the duration of the B-and C-fibre compound potentials in the isolated vagus nerve. The lack of effect on the vagus A-fibre potential may be explained by an absence of repolarizing potassium currents in these fibres as has been shown for single, rabbit (Chiu et al 1979) and rat (Brismar 1980) myelinated axons.…”
Section: A) 4-aminopyridinementioning
confidence: 73%
“…In addition, 100 j, tmol/1 4-AP clearly enhanced the duration of the B-and C-fibre compound potentials in the isolated vagus nerve. The lack of effect on the vagus A-fibre potential may be explained by an absence of repolarizing potassium currents in these fibres as has been shown for single, rabbit (Chiu et al 1979) and rat (Brismar 1980) myelinated axons.…”
Section: A) 4-aminopyridinementioning
confidence: 73%
“…Our previous studies using unmyelinated axon (HH model) (Tai et al, 2005a,b) and amphibian myelinated axon model (FH model) (Zhang et al, 2006a,b), which incorporated only fast potassium current, also showed that the fast potassium current plays a critical role. Furthermore, our study using the CRRSS model (Zhang et al, 2006b), which was derived from mammalian (rabbit) myelinated axon and did not incorporate any potassium current (Chiu et al, 1979), completely failed to simulate the nerve conduction block, further indicating a role of the potassium current. Although the small fast potassium current at the node of Ranvier of the mammalian myelinated nerve may be of importance in nerve conduction block, investigating the role of the slow potassium current is definitively warranted due to its dominant presence at the node of Ranvier (Roper and Schwarz, 1989;Schwarz et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Although it will be very difficult for studies using animals to verify the details of the blocking mechanism due to technical issues, simulation analysis using other axonal membrane models could be performed. These models include HH model (Hodgkin and Huxley, 1952), FH model (Frankenhaeuser and Huxley, 1964), CRRSS model (Chiu et al, 1979), SRB model (Schwarz et al, 1995), or MRG model (McIntyre et al, 2002, which are derived from the axon membranes of different species (squid, frog, rat, rabbit, or human). Simulation analysis using these axonal models may further reveal that different types of axons (unmyelinated, myelinated, amphibian, or mammalian) may have different blocking frequencies and different mechanisms of block.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally obtained chronaxie values using electrodes placed close to the excited axon (clamp experiments, animal studies and needle electrodes) are between 30 and 150 ls [3,9,42]. Published non-linear nerve models were experimentally verified in this range of chronaxie values [4,37,38,42,52]. However, chronaxie values that were obtained experimentally using surface electrodes are longer.…”
Section: Introductionmentioning
confidence: 98%